The era of pulmonary surfactant from Laplace to nowadays - Parmigiani, S.; Solari, E. (Acta Biomedica Atenei Parmensis, 2003)
The first observations on neonatal respiratory distress syndrome (RDS) were published by some obstetricians in England, France and Germany in the second half of the 18th century. The concept that RDS might involve the absence of something stems from the observations of a Swiss physiologist, Kurt von Neergaard, who published an article in 1929 about a fundamental principle of respiratory mechanics: the surface tension in the alveoli. Further early descriptions of the existence, composition, and synthesis of the surfactant complex and its physiologic role in maintaining alveolar stability were dependent on the pioneering contributions of Radford, Macklin, Pattle, and Clements (among others). But the final link, describing surfactant deficiency as a cause of RDS, came from Avery and Mead in 1959, when they showed lung extracts from babies with hyaline membrane disease deficient in surfactant. Understanding surfactant composition, function and therapeutic usefulness has increased exponentially over the last 50 years and this paper reorganizes the steps of the research in this field until nowadays. Most of the discussion concerns the fundamental role of lung surfactant in RDS of premature infants, and the success of exogenous surfactant replacement in the clinical therapy of this disease.